Pandangan Hukum Islam pada Tantangan Moderasi Beragama Masyarakat Bali di tengah Pandemi Covid-19 - veronica octavina; Haris Balady (Ngarsa: Journal of Dedication Based on Local Wisdom, 2021)
This article will focus the study and discussion on the principles and phenomena of Islamic moderation in Bali during the Covid-19 pandemic. This article aims to uncover and describe the various principles for the moderation of di religion that have been formulated by Islamic law experts from both Ushuliyyun and Fuqaha circles. This article also aims to present the moderating phenomena of Islamic Law in Bali during the Covid-19 Pandemic that has been demonstrated by Islamic jurisprudence scholars in the tradition of istinbath law. The method used in this study is an ethnographic approach by paying attention to culture (Anthropology) and language (Linguistics). The results showed that the plural Balinese community adopted a moderation attitude of diversity in the midst of the Covid-19 pandemic faced with a variety of different religious cultures. Keywords: Religious Moderation, Balinese Society, Covid-19 Pandemic. Abstrak Kajian ini akan memfokuskan kajian dan pembahasan pada prinsip-prinsip dan fenomena moderasi Islam di Bali saat pandemi Covid-19. Artikel ini bertujuan untuk mengungkap dan menggambarkan berbagai prinsip bagi moderasi keberagamaan yang telah dirumuskan oleh pakar hukum Islam baik dari kalangan Ushuliyyun maupun Fuqaha. Artikel ini juga bertujuan untuk mengemukakan fenomena-fenomena moderasi Hukum Islam di Bali saat Pandemi Covid-19 yang telah ditunjukkan oleh ulama fikih Islam dalam tradisi istinbath hukum. Metode yang digunakan dalam penelitian ini ialah kepustakaan. Hasil penelitian menunjukkan bahwa masyarakat Bali yang plural menerapkan sikap moderasi keberagamaan di tengah pandemi Covid-19 yang dihadapi dengan berbagai macam budaya agama yang berbeda. Kata Kunci: Moderasi Beragama, Masyarakat Bali, Pandemi Covid-19.